Treatment patterns of patients diagnosed with major headache disorders: A retrospective claims analysis - David Kudrow; Sagar Munjal; Leah Bensimon; Tasneem Lokhandwala; Binglin Yue; Anna D'Souza Coutinho; Stephen D Silberstein (SAGE Publishing, 2020)
Objective: To describe patient characteristics, treatment patterns, and health care costs among patients diagnosed with major headache disorders overall and by type (tension-type headache [TTH], migraine, cluster headache [CH], or >1 primary headache type), and secondarily to evaluate drug treatment patterns among triptan initiators with a major headache diagnosis. Methods: Using US claims data from January 2012 through December 2017, we identified adults with evidence of a major headache disorder: TTH, migraine, or CH; the first diagnosis date was deemed the index date. To evaluate triptan use specifically, patients who initiated triptans were identified; the first triptan claim date was deemed the index date. Patient characteristics, treatment patterns (concomitant treatments, adherence, number of fills), and annual health care costs data were obtained. Results: Of the 418,779 patients diagnosed with major headache disorders, the following 4 cohorts were created: TTH (8%), migraine (87%), CH (1%), and >1 primary headache type (4%). The majority used analgesic (54-73%) and psychotropic (57-81%) drugs, primarily opioids (36-53%). Headache-related costs accounted for one-fifth of all-cause costs. Of the 229,946 patients who initiated triptans, the following 7 study cohorts were analyzed: sumatriptan (68%), rizatriptan (21%), eletriptan (5%), zolmitriptan (3%), naratriptan (2%), frovatriptan (1%), and almotriptan (<1%). The major concomitant analgesic medication classes were opioids (41%) and nonsteroidal anti-inflammatory drugs (34%). Conclusion: The primary headache disorder treatment paradigm is complex, with significant variability. Predominant concomitant use of opioids and switching to opioids is of concern, necessitating solutions to minimize opioid use. Switching to non-oral/fast-acting or targeted preventive therapies should be considered.